Budaya Pela Gandong sebagai Modal Sosial dalam Hubungan antar Negeri Tihulale dan Negeri Kailolo : Analisis Sosiologi - Merti Siska Rosely (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study aims to analyze the Pela Gandong culture as social capital in the inter-village relationship between Tihulale and Kailolo from a sociological perspective. Pela Gandong is a form of local wisdom in Maluku society that functions as a value system binding solidarity, trust, and cooperation among communities. The method used in this research is a qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The results show that Pela Gandong plays a significant role as social capital in strengthening social cohesion, minimizing conflicts, and fostering harmonious relationships not only between Tihulale and Kailolo but also among other villages in Maluku, each with its own unique forms of Pela and Gandong ties. Values such as trust, shared norms, and social networks are key elements in sustaining inter-village relationships in Maluku. Furthermore, this cultural system serves as an effective local wisdom-based conflict resolution mechanism within a multicultural society. However, modernization and social change pose challenges to the internalization of these values, particularly among the younger generation. Therefore, efforts to preserve and revitalize Pela Gandong culture are essential to maintain its relevance in contemporary social life. This study emphasizes that Pela Gandong is not merely a cultural tradition but also a strategic social force in strengthening social integration and solidarity in Maluku society.